Synthesis and Antibacterial Activity of Some New Chlorosubstituted-4-Aroyl Isoxazoles - V. Parhate*, ana; Maurya, M.R.; Rajput, P.R. (Asian Journal of Chemistry, 2010)
4-Aroyl isoxazoles (2a-d) have been synthesized by the condensation of 3-aroyl flavones (1a-d) with hydroxylaminehydrochloride in DMSO containing a few drops of piperidine. Structural elucidation has been done on the basis of elemental analysis, chemical properties and spectral data, Antibacterial activities of these compounds were screened against E. coli. S. aureus. B. subtilis and P. vulgaris by disc diffusion method. These compounds showed appreciable activity towards microorganisms.